C126 - Water resources management. 10 units. [Training/Course material]. - Smith, L. (2009)
This module is about water resources, their complex relationship with the environment and the economy and the growing problem of water scarcity and the various options that exist to deal with this problem. The module examines how water is allocated between various competing demands and explores the role that water plays in food security, public health, people’s livelihoods and other aspects of social and economic development. The module seeks to critically evaluate the benefits, costs and impacts of water resources development, particularly those aspects most relevant to social and economic development in rural areas. Coverage includes the key water management challenges communities are facing today and the solutions that people have developed. Parts of the module concentrate on the ways in which economic concepts, methods and judgements can inform water resource management strategies and policy decisions that affect the resource. Economic efficiency in resource allocation is only one of many criteria used by policy-makers to evaluate the appropriate approach to a given issue. However, the insights given by the application of economic theory are often ignored in the face of conflicts over the use of water. The module also introduces a range of techniques, methods and information resources that can be used by professionals for the assessment of water resources and planning. Good information and good applied science are keys to improved water resource management and should be considered as necessary but not sufficient. It is also vital to develop the institutional arrangements and policies necessary for sustainable water use and environmental conservation. Thus governance arrangements in relation to water management are also a leading theme of the module.